Meta-Analysis of Novel Biomarkers for Early Diagnosis of Neonatal Sepsis - Rati Annisah; Ratu Hanny Anggorowati (HM Publisher, 2024)
Neonatal sepsis is a major cause of illness and death in newborns worldwide. Early diagnosis is critical for quick treatment and better outcomes. However, traditional markers like white blood cell count and immature-to-total neutrophil ratio are often not sensitive or specific enough. This meta-analysis reviewed PubMed, Embase, and the Cochrane Library from January 2013 to December 2023. It included studies that assessed the accuracy of procalcitonin (PCT), interleukin-6 (IL-6), and C-reactive protein (CRP) in diagnosing neonatal sepsis. The QUADAS-2 tool was used to check the quality of the studies. Six studies, including 1245 newborns, were analyzed. PCT had the highest pooled sensitivity (0.85, 95% CI 0.80-0.90) and specificity (0.82, 95% CI 0.75-0.89), followed by IL-6 (sensitivity: 0.78, 95% CI 0.70-0.85; specificity: 0.75, 95% CI 0.65-0.83). CRP was less sensitive (0.70, 95% CI 0.60-0.79) and specific (0.68, 95% CI 0.58-0.77). In conclusion, new biomarkers, especially PCT, are promising for early diagnosis of neonatal sepsis. However, more large-scale studies are needed to confirm these findings.